The 21st Century Reforms (Re)Shaping the Education Policy of Inclusive and Special Education in Finland - Raisa Ahtiainen; Jonna Pulkkinen; Markku Jahnukainen (MDPI AG, 2021)
In recent decades, an essential global aim of the reforms of special education has been the promotion of inclusive education. This article discusses the implementation of reforms with a focus on tiered support systems in the context of Finnish comprehensive school education. Based on earlier literature, legislation, and administrative documents, we provide a background for Finnish education policy and special education reforms. The focus of this article is on the description of parallel reforms targeting the re-structuring of the systems around support for students and funding of education in the 2010s. We discuss the processes leading to these reforms and the reforms themselves. In addition, we discuss their implications for the organization of the tiered support system. Finally, we highlight some challenges of reform implementation and the current education policy's movements towards inclusive education.